The Effect of Fiscal Services, Tax Socialization, and Tax Sanctions on Motor Vehicle Taxpayer Compliance (Case Study on SAMSAT Lubuk Linggau City) - Robi Octavianus; Harsi Romli; Muhammad Hamdan Sayadi (International Journal of Community Service & Engagement, 2022)
This Study aims to examine the effect of tax authorities, tax socialization and tax sanction on taxpayer compliance at SAMSAT Lubuklinggau City. The data collection technique used a questionnaire with a sample size of 100 people. This study implement multiple linear regression methods to analyze data. The result of this study indicate that all variables, namely tax authorities, tax socialization and tax sanction have a positive effect on taxpayer compliance. The research is expected to provide benefits to SAMSAT Lubuklinggau City to improve motor vehicle taxpayer compliance must consider tax authorities, tax socialization and tax sanctions.